Sains dan Teknologi Dalam Al-Qur'an (Kajian Filsafat Pendidikan Islam) - A. Syafi' AS (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This study aims to examine science and technology in the perspective of the Qur'an, and the positive and negative impacts on human life. This research is a library research using a qualitative descriptive approach. The data collection method uses the documentary method, and data analysis using inductive and deductive analysis. The results showed that science and technology in the perspective of the Qur'an absolutely upheld because it is very necessary in everyday life and even many provide convenience for human life. However, in its application, consideration must be given to the positive and negative impacts, so that the right policies are needed so that they are not detrimental to human life itself.